1986
DOI: 10.1007/bf00252796
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic control of bone-fracture healing under ultrasonic stimulation: An animal experimental study

Abstract: In a model of closed lower-leg fracture in rabbits and of secondary bone-fracture healing, scintigraphic control until biological healing was performed. Biological fracture healing was assumed for a region of interest (ROI)-activity ratio close to 1.0. After application of 99mTc-HEDP, 151 examinations were performed. ROI activity increased significantly until day 14 p.i. and reached the maximum value (Q = 6.44) on day 14 postfracture. Sixty-one lower leg fractures were treated by ultrasound from days 14-28 pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 4 publications
0
15
0
1
Order By: Relevance
“…Its effectiveness has been demonstrated in numerous in vivo studies [1][2][3][4][5][6][7] and supported by in vitro examinations using cell culture systems. [8][9][10][11][12] LIPUS stimulation is a noninvasive, feasible, and economical method, and it has emerged as a safer alternative to biophysical approaches, especially for patients with bone plates or pacemakers.…”
Section: Introductionmentioning
confidence: 94%
“…Its effectiveness has been demonstrated in numerous in vivo studies [1][2][3][4][5][6][7] and supported by in vitro examinations using cell culture systems. [8][9][10][11][12] LIPUS stimulation is a noninvasive, feasible, and economical method, and it has emerged as a safer alternative to biophysical approaches, especially for patients with bone plates or pacemakers.…”
Section: Introductionmentioning
confidence: 94%
“…These original findings were soon supported by Reuter et al [16,17], who found positive effects in bone in a series of animal studies that involved using a continuous ultrasound signal an order of magnitude higher than that used by Duarte [18]. Klug et al [19,20] demonstrated that ultrasound treatment delivered at an intensity of 200 mW/ cm 2 accelerated the healing of closed lower-extremity fractures in rabbits by 18%. Pilla et al [21], in a placebocontrolled study of midshaft tibial osteotomies in rabbits, found that brief periods (20 min/day) of pulsed ultrasound (a 200-μs burst of 1.5-MHz sine waves, repeated at 1 kHz), delivered at a low intensity of 30 mW/cm 2 , accelerated the recovery of torsional strength and stiffness.…”
Section: Discussionmentioning
confidence: 91%
“…Fracture healing has been accelerated by exposure to a specific pulse of extremely low‐intensity pulsed ultrasound (LIPUS) in the latter power range in both animal fracture models and clinical trials (3–9) . For example, Heckman et al reported that LIPUS treatment for 20 minutes/day at 30 mW/cm 2 led to a significant 24% reduction in the time required for clinical healing in a prospective randomized placebo‐controlled study of closed or grade I open tibial fractures (8) .…”
Section: Introductionmentioning
confidence: 99%